Analysis of anthraquinone by callus tissue of Aloe barbadensis - Supe, Ujjwala (Recent Research in Science and Technology, 2013)
Aloe barbadensis, the miracle plant, is the most widely cultivated species. Aloe-barbadensis have been widely used for medicines and cosmetics. Micropropagation studies were carried out in plant tissue culture laboratory, Department of Biotechnology, St. Thomas College, Bhilai. Murashige and Skoog media enriched with IAA, 2,4-D, NAA and Kin was studied. Leaf disc of Aloe barbadensis were used as explant. Callus cultured in 2,4-D and Kin shows maximum growth rate and highest AQ production while NAA and IAA shows poor. After 60 days it was found that callus cultured on 2,4-D (3 mgl-1) and Kin (1 mg-1) gives 8.4 µg/gm AQ however, NAA (3 mg-1) and Kin (1 mg-1) gives 5.7 µg/gm.